Pengaruh Lego sebagai Media Interaktif terhadap Peningkatan Kecerdasan Spasial-Visual dan Keterampilan Kognitif dalam Pembelajaran Geometri Bangun Ruang - Nugrahani, Arshanda Gusti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Spatial geometry requires spatial-visual intelligence and cognitive skills to work on the problems and evaluations given. Children's spatial-visual intelligence and cognitive skills are still low due to teachers' lack of attention, so there are no special learning media to improve both understandings. This study aimed to determine the effect of using educational toys, namely Lego as an interactive toy on the spatial-visual abilities and cognitive skills of grade V students at Wonosari 1 State Elementary School. The type of research used in this research is quantitative research with pre-experimental methods and One-Group Pretest-Posttest Design research design. The sample used was the entire population of 50 students. Collection techniques using pretest and posttest were analyzed using the SPSS 25 application. Analysis using paired simple t-test obtained Sig. (2-tailed) of 0.000 <0.05 so that Ha is accepted and H0 is rejected. Because there is a significant difference, lego can improve spatial-visual intelligence and cognitive skills in learning geometry build space.